Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s00240-014-0680-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of local anesthetic infiltration around nephrostomy tract on postoperative pain control after percutaneous nephrolithotomy

Abstract: The objective of the study was to investigate the effect of a long acting local anesthetic infiltration around nephrostomy tract on pain control after percutaneous nephrolithotomy. Forty-six patients with kidney stones of >2 cm undergoing single access subcostal percutaneous nephrolithotomy (PCNL) were enrolled in the study. Patients were randomized to levobupivacaine (Group I) and saline (Group II) infiltration groups. Group I patients (n = 23) had 75 mg/30 cc levobupivacaine infiltration around the access si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Pooling the data from the 2 studies [11,17] showed that there was no statistically significant difference in operation time between the experimental group and the control group (WMD 5.28, 95% CI -4.41 to 14.97, p = 0.29; fig. 4b).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Pooling the data from the 2 studies [11,17] showed that there was no statistically significant difference in operation time between the experimental group and the control group (WMD 5.28, 95% CI -4.41 to 14.97, p = 0.29; fig. 4b).…”
Section: Resultsmentioning
confidence: 99%
“…There were 4 RCTs [9,10,11,17] with 225 patients that reported the time of first analgesic. The other 2 RCTs [12,13] did not refer to the analgesic demand time.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations